Customers Satisfaction and Corporate Image in Government Initiative Influencing Customers Loyalty in Terengganu, Malaysia - Mohd Sadad, Mahmud; Hazimi, Mohd Foziah; Puspa Liza, Ghazali (2018)
Various studies have been conducted to evaluate the relationship between customers satisfaction towards big companies in Malaysia. Nevertheless, the study of customer satisfaction on services provided by the government has not been much. Furthermore, study focusing on Terengganu state administration has not yet been done. Thus, the objective of this study is to look at the effectiveness of government programs and initiatives on young people based on the quality of service offered, government corporate image, customer satisfaction as a consumer to government service and to observe customer loyalty. Quantitative data was obtained by distributing questionnaires to 100 respondents comprising participants of the Terengganu Graduate Transformation Program (TGTP) who had been more than one year following the program. The TGTP participants are university leavers who have been given the opportunity to serve in several agencies and government departments throughout Terengganu. They are given exposure to government administration in various positions in line with their education background and interest. The data were analysed using the IBM SPSS Statistics (Statistics Package for the Social Sciences) software aimed at looking at the relationship between the service aspects offered by the government through various initiatives and programs in Terengganu. The relationship is measured in order to look at the strong bonding which forms the customer loyalty behaviour. The findings show that there is a direct relationship between service quality, corporate image influencing customer satisfaction and customer loyalty.